2020
DOI: 10.1051/e3sconf/202021022028
|View full text |Cite
|
Sign up to set email alerts
|

Notes from experience in application of interactive teaching methods in university settings

Abstract: Both theory and practise agree that, in order to achieve numerous advantages of interactive teaching, it is crucial that teachers and students have experience in interactive work and posses some social competencies. Interactive teaching are ineffective when teachers lack pedagogical knowledge and experiences and when students unaccustomed to interaction in class. That is why this paper presents the most important experiences in interactive teaching practise in a university environment, shows examples of good p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Thus, Gutiérrez et al [116] concluded that an incentive for student autonomy on the part of the teacher leads to more significant commitment, participation, or engagement. Other studies also converge on the same idea [117] and relate the need to apply group work techniques in the classroom with students as a mechanism to improve their interaction [118], also pointing out how motivation and academic performance data improve due to the positive impact of techniques that promote student participation and collaboration [119,120].…”
Section: Discussionmentioning
confidence: 97%
“…Thus, Gutiérrez et al [116] concluded that an incentive for student autonomy on the part of the teacher leads to more significant commitment, participation, or engagement. Other studies also converge on the same idea [117] and relate the need to apply group work techniques in the classroom with students as a mechanism to improve their interaction [118], also pointing out how motivation and academic performance data improve due to the positive impact of techniques that promote student participation and collaboration [119,120].…”
Section: Discussionmentioning
confidence: 97%
“…It should be borne in mind that application of digital technologies and interactive approaches in teaching becomes only possible in case of due media literacy of all the participants of the learning process [10,11].…”
Section: Introductionmentioning
confidence: 99%